The Essential Is Culture, Economics Is Mediated - Aguilera, Víctor Rolando Bellido; Fernández, Adris Díaz (Journal of Applied Business and Economics, 2022)
To this purpose, the cult of production, economic efficiency and material power are described as fac- tors that have helped the full imposition of a sordid materialism, of consumerism and have propelled the social and environmental deterioration suffered by today’s society. We reflect on the original and dialectically contradictory work of Karl Marx, José Martí and Enrique Dussel, among others, while arguing in favor of the creative and socio-cultural essence of the human being, and of its complete subjectivity, to which we assign a primary role. The authors describe the conceptions and practices that make the market economy into an end by itself as “economystique”, showing they lose their way because they do not understand that both production and all scientific, technical and social activities must be conceived and carried out as means for human improvement.